Rubber Oxygenase and Latex Clearing Protein Cleave Rubber to Different Products and Use Different Cleavage Mechanisms - Birke, Jakob (American Society for Microbiology, 2014)
Two types of enzyme for oxidative cleavage of poly(cis-1,4-isoprene) are known. One is rubber oxygenase (RoxA) that is secreted by Xanthomonas sp. strain 35Y and a few other Gram-negative rubber-degrading bacteria during growth on polyisoprene. RoxA was studied in the past, and the recently solved structure showed a structural relationship to bacterial cytochrome c peroxidases (J. Seidel et al., Proc. Natl. Acad. Sci. U. S. A. 110:13833–13838, 2013, http://dx.doi.org/10.1073/pnas.1305560110). The other enzyme is latex-clearing protein (Lcp) that is secreted by rubber-degrading actinomycetes, but Lcp has not yet been purified. Here, we expressed Lcp of Streptomyces sp. strain K30 in a ΔroxA background of Xanthomonas sp. strain 35Y and purified native (untagged) Lcp. The specific activities of Lcp and RoxA were 0.70 and 0.48 U/mg, respectively. Lcp differed from RoxA in the absence of heme groups and other characteristics. Notably, Lcp degraded polyisoprene via endo-type cleavage to tetra-C(20) and higher oligo-isoprenoids with aldehyde and keto end groups, whereas RoxA used an exo-type cleavage mechanism to give the main end product 12-oxo-4,8-dimethyltrideca-4,8-diene-1-al (ODTD). RoxA was able to cleave isolated Lcp-derived oligo-isoprenoid molecules to ODTD. Inhibitor studies, spectroscopic investigations and metal analysis gave no indication for the presence of iron, other metals, or cofactors in Lcp. Our results suggest that Lcp could be a member of the growing group of cofactor-independent oxygenases and differs in the cleavage mechanism from heme-dependent RoxA. In conclusion, RoxA and Lcp represent two different answers to the same biochemical problem, the cleavage of polyisoprene, a polymer that has carbon-carbon double bonds as the only functional groups for enzymatic attack.